Use of Translational, Genetically Modified Porcine Models to Ultimately Improve Intestinal Disease Treatment - Schaaf, Cecilia R.; Gonzalez, Liara M. (Frontiers in Veterinary Science, 2022)
For both human and veterinary patients, non-infectious intestinal disease is a major cause of morbidity and mortality. To improve treatment of intestinal disease, large animal models are increasingly recognized as critical tools to translate the basic science discoveries made in rodent models into clinical application. Large animal intestinal models, particularly porcine, more closely resemble human anatomy, physiology, and disease pathogenesis; these features make them critical to the pre-clinical study of intestinal disease treatments. Previously, large animal model use has been somewhat precluded by the lack of genetically altered large animals to mechanistically investigate non-infectious intestinal diseases such as colorectal cancer, cystic fibrosis, and ischemia-reperfusion injury. However, recent advances and increased availability of gene editing technologies has led to both novel use of large animal models in clinically relevant intestinal disease research and improved testing of potential therapeutics for these diseases.